An insight into stress and strain analysis over on hexagonal aluminium sandwich honeycomb with various thickness glass fiber face sheets. (2021) - Ashraff Ali, K.S.; Suresh Kumar, S.; Allen Jeffrey, J.; Ravikumar, M.M.; Rajkumar, S.
Abstract: Aluminium honeycomb sandwich panels have greater applications for constructions and Hexagonal aluminium design of satellites, missiles, aircraft, ships and also automobiles. To prevent failure of an important structure that subjected to stress, the aluminium honeycomb sandwich panels with face sheets act as protective mechanism. It is important to go for analysis study about stress and strain distribution on aluminium honeycomb with face sheets. In this investigation, it is focused on stress and strain distribution of sandwich structures, which were constructed of hexagonal aluminium core with glass fibre face sheets. The model of hexagonal aluminium sandwich panels with glass fibre face sheets will develop by using the Pro-E software. Further the stress and strain distribution for glass fibre face sheets with aluminium honeycomb will analyze by using ANSYS software. The ANSYS analysis carried out for the face sheets of 0.5 mm, 1 mm and 1.5 mm thicknesses with hexagonal aluminium honeycomb, which should be useful effectively for various applications.